2019
DOI: 10.1039/c9ra05602e
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ZEB1-AS1 inhibits renal fibrosis in diabetic nephropathy by regulating the miR-217/MAFB axis

Abstract: Diabetic nephropathy (DN) is a common chronic microvascular complication of diabetes, characterized by the deposition of extracellular matrix (ECM) proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The present results manifested that HG-treated HCFs showed repressed ZEB1-AS1 expression, increased cell viability, promoted cell migration, and augmented levels of collagen I, collagen III, fibronectin and α-SMA, whereas these trends were negated after overexpression of ZEB1-AS1. It is consistent that the decreases in fibronectin, α-SMA, collagen I and IV protein levels, induced by ZEB1-AS1 overexpression, are observed in HG-induced human kidney-2 cells and diabetic mice 9 . ZEB1-AS1 is underexpressed in kidney tissues of patients with diabetic nephropathy, and ZEB1-AS1 overexpression inhibits HG-triggered fibrogenesis 8 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present results manifested that HG-treated HCFs showed repressed ZEB1-AS1 expression, increased cell viability, promoted cell migration, and augmented levels of collagen I, collagen III, fibronectin and α-SMA, whereas these trends were negated after overexpression of ZEB1-AS1. It is consistent that the decreases in fibronectin, α-SMA, collagen I and IV protein levels, induced by ZEB1-AS1 overexpression, are observed in HG-induced human kidney-2 cells and diabetic mice 9 . ZEB1-AS1 is underexpressed in kidney tissues of patients with diabetic nephropathy, and ZEB1-AS1 overexpression inhibits HG-triggered fibrogenesis 8 .…”
Section: Discussionsupporting
confidence: 83%
“…LncRNAs show aberrant expression patterns in diabetic cardiac tissues, and modulation of specific lncRNA expression levels causes pathophysiological changes in DCM 7 . LncRNA zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) inhibits high glucose (HG)-induced fibrogenesis and renal fibrosis in diabetic nephropathy 8,9 . Emerging evidence has shown that lncRNAs play the role of competing endogenous RNAs (ceRNAs) for microRNAs (miRNAs), and modulate their target gene expression in various diseases 10 .…”
Section: Introductionmentioning
confidence: 99%
“…118 Overexpression of ZEB1-AS1 could regulate MAF bZIP transcription factor B (MAFB) expression by directly targeting miR-217, reducing HG-induced ECM accumulation in HK-2 cells, and inhibiting renal fibrosis in DKD. 119 However, MIAT was reported to be downregulated in expression in HK-2 cells in contrast to MCs and podocytes. Myocardial infarction-associated transcript expression levels were low and negatively correlated with serum creatinine (Scr) and blood urea nitrogen in both HK-2 cells and diabetic rats.…”
Section: Lncrnas With Downregulated Expression In Renal Tubular Epith...mentioning
confidence: 99%
“…ZEB1‐AS1 can promote H3K4me3 histone modification on the ZEB1 promoter to regulate ZEB1 118 . Overexpression of ZEB1‐AS1 could regulate MAF bZIP transcription factor B (MAFB) expression by directly targeting miR‐217, reducing HG‐induced ECM accumulation in HK‐2 cells, and inhibiting renal fibrosis in DKD 119 . However, MIAT was reported to be downregulated in expression in HK‐2 cells in contrast to MCs and podocytes.…”
Section: Lncrnas Affect Various Pathologic Changes In Dkdmentioning
confidence: 99%
“…Synergizing with this mechanism, lncRNA ZEB1-AS1 that suppresses renal fibrosis, is downregulated in DN. Normally, ZEB1-AS1 sequesters miR-217 and upregulates the transcription factor MAFB (musculoaponeurotic fibrosarcoma oncogene homolog B) along with reduction in ECM proteins such as fibronectin and collagen, to inhibit renal fibrosis in DM [ 198 ]. The downregulation of ZEB1-AS1 favors renal fibrosis in DM.…”
Section: Lncrnas In Human Diseasesmentioning
confidence: 99%